Research and Analysis of Planetary Shaft Assembly Process of the Wind Power Gearbox based on the Technology of Flexible Pin - Zou Junwei; Zhu Meiling (Jixie chuandong)
The deeply analysis of the flexible pin shaft component structure of wind power gearbox planet wheel and assembly relationship are carried out,and the variable of the influence factor on the planet flexible pin assembly is confirmed.Through the experiment,the variable data is extracted,the relation curve and the function relationship between the size and temperature rise of the planet wheel pin shaft hole are obtained,the law between the flexible pin shaft sleeve and the three variables of the clearance after normal temperature,preset clearance,combination of instantaneous clearance of locating ring is found.Finally,through the simulation experiment and final assembly results,the assembly technology research scheme of planetary wheel flexible pin component is verified.